2022
DOI: 10.2298/sos2201049p
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of alkali modified fly ash and alkali activated fly ash as Zn(II) ions adsorbent from aqueous solution

Abstract: Fly ash which is solid waste can be used as an adsorbent for wastewater treatment. Alkali modification and alkali activation on fly ash can increase the adsorption capacity of fly ash. In this study, alkali modified fly ash and alkali activated fly ash were used as Zn(II) ions adsorbents. The effect of adsorption time and initial concentration of Zn(II) ions was studied, as well as the kinetics and isotherm adsorption. The results showed that the removal efficiency of Zn(II) ions by alkali ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
1
5
0
1
Order By: Relevance
“…SEM analysis to determine the surface morphology of fly ash and zeolite from fly ash had been carried out with magnification of 1000x as shown in figure 2. Fly ash had spherical shape consisting of various size with smooth surface as obtained by previous studies [12,[23][24][25]. The surface of fly ash became rough after undergoing hydrothermal process.…”
Section: Characterization Of Zeolite From Fly Ash By Hydrothermal Pro...supporting
confidence: 52%
“…SEM analysis to determine the surface morphology of fly ash and zeolite from fly ash had been carried out with magnification of 1000x as shown in figure 2. Fly ash had spherical shape consisting of various size with smooth surface as obtained by previous studies [12,[23][24][25]. The surface of fly ash became rough after undergoing hydrothermal process.…”
Section: Characterization Of Zeolite From Fly Ash By Hydrothermal Pro...supporting
confidence: 52%
“…On the basis of the R L value, adsorption process can be categorized as favorable adsorption (0<R L <1), irreversible adsorption (R L =0), linear adsorption (R L =1), and unfavorable adsorption (R L >1) (Amin et al, 2015;Purbasari et al, 2022). The comparison of obtained result in this research with the others is shown in Table 3.…”
Section: Isotherm Studies Of Mo Dye Adsorption By Fly Ash-based Geopo...mentioning
confidence: 79%
“…Figure 7-a demonstrates the effect of pH on the removal of reactive blue 19 dye effluent (250 mg/L) from an adsorption bath. Additionally, it was feasible to calculate the optimal pH value for geopolymer composite adsorption by treating dye effluent with fly ash/metakaolin-based geopolymers (FM and FM-TiO2) at a variety of pH ranges (2)(3)(4)(5)(6)(7)(8)(9)(10). According to the outcomes from Fig.…”
Section: Different Applications Of Fm and Fm-tio 2 Geopolymer Composi...mentioning
confidence: 99%
“…The ingredients of fly ash vary considerably based on the origin and composition of the coal employed during combustion. However, all fly ash contains substantial amounts of silicon dioxide (SiO2) (both amorphous and crystalline), aluminum oxide (Al2O3), iron oxide (Fe2O3), and calcium oxide (CaO) [7]. These characteristics, both physical and chemical, suggest that there may be potential for utilization and disposal.…”
Section: Introductionmentioning
confidence: 99%